ESTUDO DAS PROPRIEDADES ESTRUTURAIS E VIBRACIONAIS DO CRISTAL DE MALEATO DE GLICINA EM FUNÇÃO DA TEMPERATURA E DA PRESSÃO. - SILVA, Ronaldo (2019)
Organic salts present applicability in non-linear optical devices and pharmaceutical application. This work contains a study about structural, thermal and vibrational properties of glycinium maleate crystals (named GM crystals). Therefore, the purpose of this work is to investigate the structural and vibrational properties of GM crystals for high and lowtemperature Raman spectroscopy (298 up to 438 K and 300 up to 8 K) and high-pressure Raman spectroscopy (0 up to 10 GPa). Thus, GM crystals were grown by slow solvent evaporation method; the pH value was 1.36 to GM on 298 K. It was characterized by powder X-ray diffraction (XRD), Thermo-gravimetric (TGA), Derivative Thermogravimetry (DTG), Differential Thermal Analyses (DTA), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), and high-pressure, low and high-temperature Raman Spectroscopy. From X-ray diffraction analysis, GM crystalize in monoclinic structure, space group C2/c and eight molecules per unit cell Z = 8. Thermal analysis (TG-DTA and DSC) indicate good structural stability up to 397 K for GM crystal. GM undergoes melting process approximately at 415 K and it suffers thermal decomposition at 438 K. TG-DTA, Raman and XRD analysis at room temperature were performed for the glycine and maleic acid to support on the comprehension of GM characterization. FTIR and Raman spectroscopy put forward the existence of functional groups exhibited for the GM, whose suggest that GM crystal suffers conformational changes beginning at 408 K. GM crystal seems undergoes phase transformation or structural rearrangement at 418 K, our conclusion is based on significant changes in bands associates with CH, CH2, NH3+ and COO- vibrations on the hightemperature Raman spectra. This was supported by high-temperature XRD (299 up to 423 K). Low-temperature Raman spectroscopy no indicates phase transition for GM crystal in the temperature range of 300 and 8 K. High-pressure Raman spectroscopy appoints to some structural rearrangements on 0.3, 2.3 and 2.7 GPa, and also reversible phase transitions on 1.7, 4.8 and 6.8 GPa due to bands that disappeared, splittings of the bands and discontinuity of the wavenumbers under pressure variations.